2012
DOI: 10.2131/jts.37.1275
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury induces CCL2 expression through activation of NF-κB in human 1321N1 astrocytes

Abstract: -Methylmercury is an environmental pollutant that is toxic to the central nervous system; however, the molecular mechanisms underlying its toxicity remain unclear. Methylmercury increases expression of several chemokines in the cerebellum of mice treated with methylmercury. The present study analyzes the mechanism underlying methylmercury-induced chemokine expression using human 1321N1 astrocytes, and shows that methylmercury increases CCL2 expression in these cells. The transcription factor NF-κB is involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The present study showed that exposure to a non-cytotoxic dose (4 μM) of MeHg activated IL-6 and MCP-1 mRNA expressions at 6 h, and subsequently, protein synthesis at 12 h. This MeHg level was within the range reported in previous studies, from 2.5 to 10 μM, in which these cytokines were induced in various glial cell lines [7,14,16,26]. Recently IL-6 production due to low dose of MeHg-treatment in astrocytes was reported to have a protective role against neurotoxicity [29,33].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The present study showed that exposure to a non-cytotoxic dose (4 μM) of MeHg activated IL-6 and MCP-1 mRNA expressions at 6 h, and subsequently, protein synthesis at 12 h. This MeHg level was within the range reported in previous studies, from 2.5 to 10 μM, in which these cytokines were induced in various glial cell lines [7,14,16,26]. Recently IL-6 production due to low dose of MeHg-treatment in astrocytes was reported to have a protective role against neurotoxicity [29,33].…”
Section: Discussionsupporting
confidence: 87%
“…Monocyte chemoattractant protein (MCP)-1 also seems to be important in various neuroinflammatory diseases [10]. Recently, an elevation of MCP-1 expression in response to MeHg exposure was observed in mice experiment (10 mg/kg/day for 7 days) [22] and human 1321N1 astrocytoma cells (10 μM for 6 h) [26]. It was also reported to work as an alert system for MeHg exposure, using MCP-1-knockout mice [18].…”
Section: Introductionmentioning
confidence: 99%
“…The biological factors that are altered by MeHg have been explored with the aim of shedding light on the molecular mechanisms that underlie MeHg toxicity (Hwang et al, 2011a(Hwang et al, , 2013aHwang and Naganuma, 2006;Kim et al, 2012Kim et al, , 2013Lee et al, 2012;Takahashi et al, 2013;Toyama et al, 2011). Furthermore, the research group led by Dr. Naganuma has found a large number of proteins that are resistant or hypersensitive to MeHg (Hwang et al, 2007(Hwang et al, , 2010a(Hwang et al, , 2010b(Hwang et al, , 2010c(Hwang et al, , 2011b(Hwang et al, , 2012a(Hwang et al, , 2012b(Hwang et al, , 2013b.…”
Section: Attempts To Identify Cases Of the S-mercuration Of Proteinsmentioning
confidence: 99%
“…Multiple studies have reported that NF-κB signaling has a central role in the transactivation of CCL2, [39][40][41][42][43] which attracted us to examine whether PKM2-dependent expression of CCL2 could be attributed to the upregulation of NF-κB signaling. Luciferase activities were highly significantly upregulated in all p65 expression groups compared to control group, while the group treated with siPKM2 and p65 plasmid were decreased compared to paired control.…”
Section: Pkm2 Is Required For Binding Of P65 Nf-κb To Ccl2 Promotermentioning
confidence: 99%